Food Particle Aspiration Associated with Hemorrhagic Shock: A Diagnostic Dilemma. (19th May 2015) - Tashtoush, Basheer; Schroeder, Jonathan; Memarpour, Roya; Oliveira, Eduardo; Medina, Michael; Hadeh, Anas; Ramirez, Jose; Smolley, Laurence
Abstract : The hemodynamic compromise caused by a large aspirated food particle in the airway can become the focus of medical attention and a distraction from rare but fatal Heimlich maneuver related injuries after an incident of food aspiration. We herein present a case of an 84-year-old man who was brought to the emergency department after an episode of choking at a restaurant followed by several failed Heimlich maneuver attempts. Despite relieving the airway obstruction by extracting a large piece of steak from the airway, the patient remained hypotensive and required continued hemodynamic support. Repeated laboratory tests within 24 hrs of aspiration showed a significant decline in the hemoglobin level. A computed tomography (CT) scan of the abdomen and pelvis showed a lacerated liver with a large subcapsular hematoma draining into the pelvis. Conclusion . Hepatic rupture is a rare complication of Heimlich maneuver; this paper represents the second case report in the literature. It emphasizes the necessity of early identification and surveillance of fatal Heimlich maneuver complications in a high risk population.